Understanding local performance data for EBUS-TBNA: insights from an unselected case series at a high volume UK center - Jeebun, Vandana; Harrison, Richard Neil (Journal of Thoracic Disease, 2017)
Background: We reviewed the diagnostic performance of endobronchial ultrasound transbronchial aspiration (EBUS-TBNA) on an unselected large cohort of patients who underwent the procedure in our institution in the past 3 years and to compare against published standards and existing literature. Methods: All consecutive patients who underwent EBUS from January 2013 to December 2015 were included in the retrospective analysis, with a minimum of 6 months of clinico-radiological follow up. For assessing EBUS-TBNA performance, patients were analysed in three subgroups based on the indication for the EBUS-TBNA: in investigation of isolated mediastinal and/or hilar lymphadenopathy (IMHL), in staging of suspected or confirmed non-small cell lung cancer (NSCLC) and in making a tissue diagnosis in suspected thoracic or extrathoracic cancer. For patients subjected to EBUS-TBNA for staging in suspected lung cancer, accuracy of EBUS was measured by its ability to determine the true N2 stage. Results: A total of 1,656 lymph nodes and 138 peribronchial/peritracheal masses were sampled in 940 patients over the study period. The prevalence of reactive lymphadenopathy was 34%. The overall sensitivity to detect pathological disease was 81.6% (95% CI: 74.2–87.6%) whilst NPV was 74.8% (95% CI: 65.2–82.8%). Amongst patients who underwent EBUS-TBNA for staging purposes, the sensitivity for N2 staging was 83.7% (95% CI: 76.2–89.6%) and NPV was 81.6% (95% CI: 73.2–88.2%). The prevalence of N2 disease was 58%. In the subgroup of patients who proceeded to surgical sampling, the sensitivity was higher with the N2/N3 disease prevalence of 67.4%. The sensitivity of EBUS-TBNA to make a tissue diagnosis of thoracic or extrathoracic cancer was 88% (95% CI: 85.1–90.5%) and a NPV of 62% (95% CI: 54.7–69.0%). The disease prevalence was 83.6%. Conclusions: This retrospective study of a large volume of patients represents real life practice and provides an accurate representation of the typical cohort of patients referred in for EBUS-TBNA to the general respiratory physician in UK. Our study highlights the pitfalls in collecting and analyzing data but also demonstrates how they can be used to improve service performance.